Dentist laboratory communication - Sabah A Ismail; Abdul-Haq A Suliman (University of Mosul, College of Dentistry, 2004)
The aim of this study was to evaluate the common errors that may occur during crown and bridge construction. Four hundred stone models were used in this study for fabrication of 265 bridges and 135 single crown. The total number of units was 1141. Four main parameters were evaluated for each stone model: General information about the case, the condition of the stone model, the type of impression material and the prepared abutment tooth. The result of this study showed that 33.7% of the models were one unit and 48.7% of the models were 2-4 units and the remaining 17.5% of the models were more than five units, 8.7% of the models were without opposing arch. Alginate impression materials were used in 95% of the cases and only 5% of the cases elastomeric impression material were used. The finishing line was absent in 19.7% of the cases. Enough tooth reduction was done in 61.3% of the cases and 16.3% of the cases showed too much tooth reduction while 22.4% of the cases the tooth reduction was not enough. In order to avoid these errors continuous education courses and journal club are highly recommended.